PREDIKSI DISKALKULIA MENGGUNAKAN JARINGAN SYARAF TIRUAN BACKPROPAGATION - Deddy Kusbianto ,Nurul Khotimah (STMIK YADIKA BANGIL, 2014)
There is a gold period in which is increasing significantly development of children. At the age of four until six years, the children began to be introduced to reading, writing, and mathematic, which is an essential component for the development of children’s education. Because of that, it’s crucial to formulate a research problem on how to prediction the type learning disabilities in order to get suitable method early.This prediction the type learning disabilities using artificial neural networks with backpropagation method. Programming language used is Visual Basic. By talking the object of research on age of 4-6 years old.Result of analysis showed that: 1) Type prediction system of discalculia can be done with backpropagation neural networks method. 2) 20 data that trained were 6 data does not match the desired output. While there are 14 data in accordance with the desired output.Keywords: Discalculia,Neural Network, Backpropagation